LOW COST REAL-TIME MEASUREMENT OF THE ECG, SPO2 AND TEMPERATURE SIGNALS IN THE LABVIEW ENVIRONMENT FOR BIOMEDICAL TECHNOLOGIES EDUCATION - CİKLACANDİR, Samet; MULAYİM, Naciye; SAHİN, Savas (The Eurasia Proceedings of Educational and Social Sciences, 2017)
Electrocardiography (ECG) is to measure the electrical activity of the heart. Doctors diagnose various cardiac diseases by analyzing this signal. The ECG signal is one of the best diagnostic devices for heart diseases. The purpose of this work is to display the ECG signal in the LabVIEW (Laboratory Virtual Instrument Engineering Workbench) environment. Lowering the cost by designing your own ECG circuit. The program can also easily process the ECG signal in various ways. There is no need to setup any electronic circuit. In addition to the ECG signal, modules with pulse oximeter and temperature indicating oxygen saturation are added. In this study, low cost ECG, temperature and pulse measurements were performed in our own laboratory environment. The measurement circuit was communicated with the LabVIEW program via Arduino. The data received with Arduino is shown after processing in the LabVIEW environment. The program also shows the patient's heart rate and alerts when the patient enters a heart attack.